Dampak Pola Asuh Orang Tua Terhadap Perilaku Beragama Siswa - Farichah, Siti Dawiyah; Neima, Emiliano Ihza Siar (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
The formation of adolescent religious behavior is shaped by several factors, one of which is the family environment. The family environment, especially parents, plays an important role in shaping children's religious behavior. This is the background for carrying out this research. The research aims to describe the impact of parental parenting on students' religious behavior and to describe the factors that influence the formation of students' religious behavior, taking as subjects students of class X IPS MAN 2 Jember. The research uses descriptive qualitative methods with data collection techniques of observation, interviews and documentation. The data obtained was analyzed in stages: data reduction, data presentation, and verification, while in the data validity process, source triangulation and technical triangulation were used. Research produces findings that parenting styles have an impact in shaping students' religious behavior. An authoritarian parenting style that is applied using violence produces children who have quiet personalities. Permissive parenting has an impact on children who are spoiled and lack awareness of responsibility. Democratic parenting produces children who have an open personality and likes to help others, while Islamic parenting produces children who reflect the figure of a Muslim. The next finding is that there are several factors that influence the formation of students' religious behavior, including: family environment, community environment (including friends and cellphones), madrasa environment (teachers and friends).